ANALYZING THE USES OF FACEBOOK ADVERTISING AS A SOCIAL MEDIA MARKETING TECHNIQUE OF A BANK: A STUDY ON A PRIVATE BANK LIMITED - Mamun, Abdullah Al; Saha, Apu Chandra; Islam, Asraful (International Journal of Marketing Research Innovation, 2022)
In the era of globalization, the media is the essential fact of advertising in the competitive market. The main objective of this report is to analyze the uses of Facebook Advertising as a Social Media Marketing Techniques of a private bank. Data were collected using a survey questionnaire. The targeted respondents of this study were bank employees of a private bank, the Lohagara-Narail branch. Both male and female respondents have answered the questionnaire. Data were analyzed quantitatively using SPSS, which was a statistical method for analyzing numerical data. Both primary and secondary data were necessary for the fulfillment of the research project. Secondary data were collected from various published documents in related books, journals, social media, and websites. For getting primary data, respective respondents were interviewed personally to collect the data required through a structured questionnaire with marketing experts and employees from some reputed and leading companies that were descriptive research question and also a face-to-face interview with the customers that was exploratory research question. A five-point Likert scale has been used for study purposes. To attain customer attention, Facebook marketing is directly associated with the benefits of the social media platform. From this study, the employee and customers can know about Facebook Advertising as a Social Media Marketing Techniques.JEL Classification Codes: M31.